Association between Oral Mucosal Lesions and Hygiene Habits in a Population of Removable Prosthesis Wearers - ERÇALIK YALÇINKAYA, ŞEBNEM (WILEY, 2015)
PurposeThis prospective study evaluated the influence of self-reported prosthesis hygiene regimens and prosthesis usage habits on the presence of oral mucosal lesions (OMLs) in complete removable and/or partial removable dental (CRDP/PRDP) prosthesis wearers (PWs). Materials and MethodsBetween January 2009 and January 2011, the conventional oral mucosa of 400 consecutive PWs (252 women; 148 men), aged between 29 and 86 years, were examined clinically. Information was derived considering the type and age of the prosthesis, hygiene level, frequency and style of prosthesis cleaning, overnight prosthesis use, storage conditions, and systemic diseases. Non-prosthesis- and prosthesis-related OMLs were identified. The data were analyzed using univariate (Chi-square) and multivariate (logistic regression) tests to assess the development of OMLs as a function of the selected variables. Odds ratios (OR) were calculated at 95% confidence intervals (CI; = 0.05). ResultsOf the 400 PWs, 21.5% had CRDP, 52.5% PRDP, and 25.8% CRD/PRD prostheses. Thirty-two percent of the PWs cleaned their prosthesis once a day. Brushing the prosthesis with toothbrush and soap/toothpaste was the most commonly practiced cleaning regimen (85.8%). More than half (64.5%) of the PWs used their prosthesis overnight. Among all PWs, 37.8% had a prosthesis-related OML. Stomatitis Newton Type II (46%) and Type III (38%) were the most common OMLs. OML frequency was higher in PWs having CRDPs than those having PRDPs (p < 0.05). Overnight prosthesis use (p = 0.003, OR: 13.65; 95% CI: 1.7-109.3), denture age 11 years (p = 0.017, OR: 1.72; 95% CI: 1.1-2.7), and immersion in water and solution (p = 0.023, OR: 1.13; 95% CI: 0.02-1.02) affected the incidence of OML significantly. Hypertension was the most common systemic disease (31.5%). ConclusionOvernight use, denture age, and storage conditions of CRDP or PRDPs demonstrated a more significant impact on OML incidence than frequency of cleaning. Oral healthcare programs for removable PWs should specifically provide education on prosthesis usage instructions.
Keywords: Aged; complete; partial removable prosthesis; dental care for aged; oral mucosal lesions; stomatitis; COMPLETE DENTURE WEARERS; ELDERLY POPULATION; HEALTH STATUS; OLDER-PEOPLE; PREVALENCE; STOMATITIS; RISK; CLEANLINESS; DENTISTRY; ISTANBUL